Identification of lesion components that influence visual function in age related macular degeneration. Issue 5 (1st May 2003) - Hogg, R; Curry, E; Muldrew, A; Winder, J; Stevenson, M; McClure, M; Chakravarthy, U
Abstract : Aims: To explore the relation between lesion composition as assessed by fundus photography and fluorescein angiography with clinical measures of vision in eyes of patients with age related macular degeneration (AMD). Methods: A standardised visual function assessment along with colour stereo pair fundus photography was carried out in both eyes of 58 subjects with a confirmed clinical diagnosis of AMD. The size, location, and composition of the macular lesion (blood, exudate, subretinal fluid, pigment, membrane, atrophy, and fibrosis) were measured on the colour photographs using computer assisted image analysis. Of the 58 subjects, 44 also had concurrent fluorescein angiography. Classic and occult choroidal neovascularisation (CNV), blood, blocked fluorescence, fibrosis, geographic atrophy, and the total area of abnormal fluorescence were measured. Multiple linear regression was used to examine the relation between clinical measures of vision and the location and extent of lesion components identified by both colour and fluorescein image capture. Results: The composition of the macular lesion strongly influenced visual function, with atrophy (p=0.001) and fibrosis (p=0.002) accounting for most of the variation. When the location of the lesion with respect to the fovea was examined, fibrosis within the fovea significantly influenced all clinical measures of vision (p=0.008). The regression model selected the total area of abnormal fluorescence and a composite parameter (a semiquantitative measure of the following characteristics: atrophy, exudates, blood, and fibrosis ) from colour photography ( r 2 =0.52) as the variables that explained most of the variation in clinical measures of vision. Conclusions: The composition and extent of the macular lesion strongly influences visual function in eyes with AMD. Both colour photography and angiography yielded information, which together explained considerably more of the variation in the clinical measures of vision than either on its own.